Determinants of Perceptions of Poverty; A Case of Townships in Gauteng Province of South Africa - Dunga, Hannah M.; Dunga, Steven H. (International Journal of Economics and Financial Issues, 2022)
Poverty reduction policies and interventions are only effective if the poor themselves own the process and believe in the process being implemented. The way people perceive poverty is to a greater extent informed by their position and economic circumstances in society. The conservative theorist of poverty argue that the poor are lazy and hence would tend to blame the society and the structures thereof. Assertions in the culture of poverty by Oscar Lewis imply that the poor may become comfortable in their poverty and hence may ignore any efforts that would change their circumstances. The liberal theories on the other hand argue that those in poverty perceive poverty as a result of an evil and an unequal system. However, these are general expectations and yet they are not always the same across countries and regions. This paper examines the perceptions of the causes of poverty as conceived by the people living in selected South African townships. The paper used data that was collected in the Gauteng Province South Africa in 2019-2020. Based on the Feagin scale of perceptions of the causes of poverty, the main categories namely, fatalistic, structural and individualistic, are considered between the different households. The results show that the poor to a greater extend agree with the structural perceptions of causes of poverty whilst those that are above the poverty line assign their position to hard work and hence blame the poor for their own circumstances mostly agreeing with the individualistic perception of causes of poverty.